LUBAC-mediated M1 Ub regulates necroptosis by segregating the cellular distribution of active MLKL - Nadine Weinelt; Kaja Nicole Wächtershäuser; Gulustan Celik; Birte Jeiler; Isabelle Gollin; Laura Zein; Sonja Smith; Geoffroy Andrieux; Tonmoy Das; Jens Roedig; Leonard Feist; Björn Rotter; et al. (Cell Death and Disease, 2024)
Abstract Plasma membrane accumulation of phosphorylated mixed lineage kinase domain-like (MLKL) is a hallmark of necroptosis, leading to membrane rupture and inflammatory cell death. Pro-death functions of MLKL are tightly controlled by several checkpoints, including phosphorylation. Endo- and exocytosis limit MLKL membrane accumulation and counteract necroptosis, but the exact mechanisms remain poorly understood. Here, we identify linear ubiquitin chain assembly complex (LUBAC)-mediated M1 poly-ubiquitination (poly-Ub) as novel checkpoint for necroptosis regulation downstream of activated MLKL in cells of human origin. Loss of LUBAC activity inhibits tumor necrosis factor α (TNFα)-mediated necroptosis, not by affecting necroptotic signaling, but by preventing membrane accumulation of activated MLKL. Finally, we confirm LUBAC-dependent activation of necroptosis in primary human pancreatic organoids. Our findings identify LUBAC as novel regulator of necroptosis which promotes MLKL membrane accumulation in human cells and pioneer primary human organoids to model necroptosis in near-physiological settings.